Immunoproteomics Analysis of the Murine Antibody Response to Vaccination with an Improved Francisella tularensis Live Vaccine Strain (LVS) - Twine, Susan M. (Public Library of Science, 2010)
BACKGROUND: Francisella tularensis subspecies tularensis is the causative agent of a spectrum of diseases collectively known as tularemia. An attenuated live vaccine strain (LVS) has been shown to be efficacious in humans, but safety concerns have prevented its licensure by the FDA. Recently, F. tularensis LVS has been produced under Current Good Manufacturing Practice (CGMP guidelines). Little is known about the immunogenicity of this new vaccine preparation in comparison with extensive studies conducted with laboratory passaged strains of LVS. Thus, the aim of the current work was to evaluate the repertoire of antibodies produced in mouse strains vaccinated with the new LVS vaccine preparation. METHODOLOGY/PRINCIPAL FINDINGS: In the current study, we used an immunoproteomics approach to examine the repertoire of antibodies induced following successful immunization of BALB/c versus unsuccessful vaccination of C57BL/6 mice with the new preparation of F. tularensis LVS. Successful vaccination of BALB/c mice elicited antibodies to nine identified proteins that were not recognized by antisera from vaccinated but unprotected C57BL/6 mice. In addition, the CGMP formulation of LVS stimulated a greater repertoire of antibodies following vaccination compared to vaccination with laboratory passaged ATCC LVS strain. A total of 15 immunoreactive proteins were identified in both studies, however, 16 immunoreactive proteins were uniquely reactive with sera from the new formulation of LVS. CONCLUSIONS/SIGNIFICANCE: This is the first report characterising the antibody based immune response of the new formulation of LVS in the widely used murine model of tularemia. Using two mouse strains, we show that successfully vaccinated mice can be distinguished from unsuccessfully vaccinated mice based upon the repertoire of antibodies generated. This opens the door towards downselection of antigens for incorporation into tularemia subunit vaccines. In addition, this work also highlights differences in the humoral immune response to vaccination with the commonly used laboratory LVS strain and the new vaccine formulation of LVS.